Hepatic-Specific Decrease in the Expression of Selenoenzymes and Factors Essential for Selenium Processing After Endotoxemia - Sherlock, Laura G.; Sjostrom, Kara; Sian, Lei; Delaney, Cassidy; Tipple, Trent E.; Krebs, Nancy F.; Nozik-Grayck, Eva; Wright, Clyde J. (Frontiers in Immunology, 2020)
Background: Selenium (Se) levels decrease in the circulation during acute inflammatory states and sepsis, and are inversely associated with morbidity and mortality. A more specific understanding of where selenoproteins and Se processing are compromised during insult is needed. We investigated the acute signaling response in selenoenzymes and Se processing machinery in multiple organs after innate immune activation in response to systemic lipopolysaccharide (LPS). Methods: Wild type (WT) adult male C57/B6 mice were exposed to LPS (5 mg/kg, intraperitoneal). Blood, liver, lung, kidney and spleen were collected from control mice as well as 2, 4, 8, and 24 hours after LPS. Plasma Se concentration was determined by ICP-MS. Liver, lung, kidney and spleen were evaluated for mRNA and protein content of selenoenzymes and proteins required to process Se. Results: After 8 hours of endotoxemia, plasma levels of Se and the Se transporter protein, SELENOP were significantly decreased. Consistent with this timing, the transcription and protein content of several hepatic selenoenzymes, including SELENOP, glutathione peroxidase 1 and 4 were significantly decreased. Furthermore, hepatic transcription and protein content of factors required for the Se processing, including selenophosphate synthetase 2 (Sps2), phosphoseryl tRNA kinase (Pstk), selenocysteine synthase (SepsecS) and selenocysteine lyase (Scly) were significantly decreased. Significant LPS-induced downregulation of these key selenium processing enzymes was observed in isolated hepatocytes. In contrast to the acute and dynamic changes observed in the liver, selenoenzymes did not decrease in the lung, kidney or spleen. Conclusion: Hepatic selenoenzyme production and Se processing factors decreased after endotoxemia. This was temporally associated with decreased circulating Se. In contrast to these active changes in the regulation of Se processing in the liver, selenoenzymes did not decrease in the lung, kidney or spleen. These findings highlight the need to further study the impact of innate immune challenges on Se processing in the liver and the impact of targeted therapeutic Se replacement strategies during innate immune challenge.